2014
DOI: 10.1002/nau.22569
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vaginal pelvic organ prolapse surgery on sexual function

Abstract: Surgical intervention for POP improved the vaginal and sexual matters scores at 6 and 12 months postoperatively. Levator plication additionally to posterior vaginal repair is associated with an increase in postoperative dyspareunia rates and with decreased sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
7
16
0
Order By: Relevance
“…Similar results have been reported elsewhere [35,36,42]. This observation of improvement may be reassuring to the patient and clinician and may very well motivate more women suffering from POP to seek help.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results have been reported elsewhere [35,36,42]. This observation of improvement may be reassuring to the patient and clinician and may very well motivate more women suffering from POP to seek help.…”
Section: Discussionsupporting
confidence: 87%
“…Follow-up rates in LMICs are typically lower than those in high-income countries (HICs) although even follow-up rates vary considerably in HICs [36,37]. In this study, the decline in further participation, lost to follow-up for unknown reasons and relocation were the reasons for leaving the follow-up schedule.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A meta-analysis of native tissue repair for prolapse and sexual function assessed dyspareunia before and after native tissue repair and reported that 47 % of women showed improvement, 39 % no change, 18 % deterioration, and 4 % had new-onset dyspareunia [21]. Ulrich showed that women who underwent vaginal repair with and without mesh reported that their sexual matters score improved significantly and their sexual bother decreased at 12 months [22]. Similarly, PISQ scores in 80 women who underwent vaginal and abdominal prolapse repair reported equivalent and significant improvement in PISQ scores at 6 months [4].…”
Section: Discussionmentioning
confidence: 99%
“…25 Similar to this study, several recent publications offer stronger evidence for improvement in quality of life: Larson et al reported high satisfaction rates eight years after sacrospinous ligament suspension, even in those women with pelvic floor defects at the hymenal ring after surgery. 26 Ulrich and colleagues reported that improvements in vaginal and sexual function depended on the type of repair, with patients undergoing levator plication reporting less benefit compared to women undergoing posterior prolapse repairs without levator plication 27 . Our study adds a large sample of highly characterized patients reporting improvement using standardized validated questionnaires.…”
Section: Discussionmentioning
confidence: 99%